2013
DOI: 10.1517/13543784.2013.778972
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor is an attractive target for the treatment of pulmonary fibrosis

Abstract: HGF with its anti-fibrotic effect provides a promising new therapeutic approach by protecting lung from fibrotic remodeling and also promoting normal regeneration of lung. The development of HGF mimetics may provide a potential attractive therapy for treatment of this devastating and complex disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 113 publications
0
39
0
Order By: Relevance
“…HGF exhibits potent cytoprotective properties in airway epithelial cells and has been used in numerous experimental and clinical applications [17,26,30,31]. However, because exogenous HGF is extremely unstable, with a half-life of 3-5 min in the circulation, it is nearly impossible to sustain a constantly high level of HGF in the circulation, even when using FIG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HGF exhibits potent cytoprotective properties in airway epithelial cells and has been used in numerous experimental and clinical applications [17,26,30,31]. However, because exogenous HGF is extremely unstable, with a half-life of 3-5 min in the circulation, it is nearly impossible to sustain a constantly high level of HGF in the circulation, even when using FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Among the biological activities of HGF, its antifibrogenic effects are also widely known [17]. HGF-MSCs exhibit anti-fibrotic properties in experimental models of lung, kidney, heart, skin, and liver fibrosis [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the paracrine factors of MSCs have anti-apoptotic effects in vitro on cardiac cells (27,28), pancreatic ÎČ cells (29) and hepatocytes (19). BM-MSCs are known to produce several epithelial specific growth factors, including HGF and KGF (17,18), which have been proven to initiate a variety of biological responses including migration, proliferation, and morpho genesis in AECs (30)(31)(32)(33). Therefore it can be speculated that the protective roles of MSC-CM on AECs may be associated with the epithelial specific growth factors secreted by BM-MSCs and the synergistic effects of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte growth factor (HGF) is a well-recognized factor that has the capacity to protect against fibrosis probably by promoting cell proliferation and survival, preventing the epithelial-mesenchymal transition, and by -its pro-angiogenic activity (Chakraborty et al, 2013). Our previous research has shown that HGF-modified MSCs (MSCs/HGF), generated by the transfection of an HGF cDNA-containing vector into MSCs, exhibit potent immunosuppressive activity (Bian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%